Bounds of Double Integral Dynamic Inequalities in Two Independent Variables on Time Scales - S. H. Saker (Discrete Dynamics in Nature and Society)
Our aim in this paper is to establish some explicit bounds of the unknown function in a certain class of nonlinear dynamic inequalities in two independent variables on time scales which are unbounded above. These on the one hand generalize and on the other hand furnish a handy tool for the study of qualitative as well as quantitative properties of solutions of partial dynamic equations on time scales. Some examples are considered to demonstrate the applications of the results.